Characterization of Induced Sugarcane Somaclones and their Sources Varieties Using Random Amplified Polymorphic DNA - Mahmud, Kuasha; Nasiruddin, KM; Hossain, MA; Hassan, L (Plant Tissue Culture and Biotechnology, 2016)
Sugarcane somaclones and their sources varieties were analyzed by RAPD molecular markers to check the variation at molecular level based on 1.4% agarose gel electrophoresis (AGE). Six RAPD primers generated 237 bands with average 39.5 varied from 15 to 63 with size ranging 145 - 1000 bp among the four sugarcane varieties and their 12 somaclones. Genetic diversity or polymorphism information content (PIC) value ranged from 0.39 to 0.50 for all loci across the 4 varieties and their 12 somaclones based on RAPD markers. Dendrogram based on linkage distance using unweighted pair group method of arithmetic means (UPGMA) based on 6 RAPD primers indicated segregation of the 4 sugarcane varieties and their somaclones into two main clusters at linkage distance 36. Variety Isd 39 was observed in main cluster C1 while its (Isd 39) somaclones and other varieties (Isd 37, Isd 38 and Isd 40) and also their somaclones were found in main cluster C2 having different sub-clusters. Theirfore, it may be concluded that RAPD markers can be used for identification of somaclonal variation and the relationship between sources varieties and their somaclones. Plant Tissue Cult. & Biotech. 25(2): 223-229, 2015 (December)